Analysis Of Curriculum Development And Learning Planning - Ulandari, Marianti; Situngkir, Christin; Permatasari, Desy; Tampubolon, Putra Novando; Simamora, Maria Dwi; Sibagariang, Susy Alestriani (Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is motivated by the importance of the curriculum as a set of subjects and educational programs provided by an educational institution, containing lesson plans to be delivered to students over a period of education. The purpose of this research is to understand the curriculum and learning planning. The research method used is descriptive qualitative, describing phenomena and existing literature.The success of a curriculum depends heavily on how it is implemented. No matter how well-designed a written curriculum is, if its implementation is not supported by various elements, it will struggle to achieve the desired results.As a tool and guide for education, the curriculum's content must align with its objectives. Because of the curriculum's crucial function and role, every curriculum development at any level must be based on specific principles. Learning is essentially an effort to teach students, and learning design is the organization of this effort to foster learning behaviors. The goal of creating a learning plan is to achieve learning improvements.This learning improvement is expected to improve the quality of learning conducted by learning designers. Curriculum developments are aligned with scientific developments.The curriculum needs to be developed dynamically to meet demands, and curriculum changes must refer to the legal sources, namely Pancasila and the 1945 Constitution